Resource: A multi‐species multi‐timepoint transcriptome database and webpage for the pineal gland and retina. Issue 3 (8th July 2020) - Chang, Eric; Fu, Cong; Coon, Steven L.; Alon, Shahar; Bozinoski, Marjan; Breymaier, Matthew; Bustos, Diego M.; Clokie, Samuel J.; Gothilf, Yoav; Esnault, Caroline; Michael Iuvone, P.; Mason, Christopher E.; et al.
Abstract: The website and database https://snengs.nichd.nih.gov provides RNA sequencing data from multi‐species analysis of the pineal glands from zebrafish ( Danio rerio ), chicken (White Leghorn), rat ( Rattus nove gicus ), mouse ( Mus musculus ), rhesus macaque ( Macaca mulatta ), and human ( Homo sapiens ); in most cases, retinal data are also included along with results of the analysis of a mixture of RNA from tissues. Studies cover day and night conditions; in addition, a time series over multiple hours, a developmental time series and pharmacological experiments on rats are included. The data have been uniformly re‐processed using the latest methods and assemblies to allow for comparisons between experiments and to reduce processing differences. The website presents search functionality, graphical representations, Excel tables, and track hubs of all data for detailed visualization in the UCSC Genome Browser. As more data are collected from investigators and improved genomes become available in the future, the website will be updated. This database is in the public domain and elements can be reproduced by citing the URL and this report. This effort makes the results of 21st century transcriptome profiling widely available in a user‐friendly format that is expected to broadly influence pineal research.